TOWARD AN INTEGRATED FINANCIAL STRATEGY FRAMEWORK FOR ACCOUNTABILITY AND BUSINESS SUSTAINABILITY: A SYSTEMATIC LITERATURE REVIEW - Dinda Ayu Izmi; Devi Trenggani; Fenny Noor Salam (INJOSEDU: International Journal of Social and Education, 2026)
This study aims to systematically review and synthesize the existing literature on financial integration and operational optimisation in relation to accountability and sustainable business models. Using a qualitative library research approach, this study analyzes peer-reviewed articles retrieved from major academic databases to identify dominant themes, theoretical foundations, methodological trends, and emerging research directions. The analysis reveals four key thematic clusters: financial integration and corporate accountability; operational optimisation and efficiency enhancement; sustainability-oriented business models; and digital transformation as an enabling mechanism. The findings demonstrate that financial integration enhances transparency, governance quality, and stakeholder trust, while operational optimisation improves resource efficiency, organizational resilience, and competitive advantage. Moreover, digital technologies play a critical role in strengthening real-time financial monitoring, predictive planning, and sustainability performance measurement. Despite the growing volume of research, the literature remains fragmented, lacking holistic conceptual frameworks that integrate economic, operational, and sustainability dimensions. This study contributes by consolidating dispersed research streams into an integrated conceptual framework, offering theoretical insights, managerial implications, and policy recommendations to advance accountable and sustainable business practices. The findings provide a robust foundation for future empirical research and strategic implementation in dynamic and sustainability-driven business environments.